Endoscopic stent placement in the management of esophagojejunal anastomosis leakage - Dobrzhanskyi, O.; Kondratskyi, Y.; Kozak, E.; Kolesnyk, A.; Pepenin, M.; Shudrak, Y.; Horodetskyi, A.; Turchak, V.; Omelchak, A.; Koval, N.; Svichkar, Y.; Ukrainets, I. (General Surgery, 2024)
Objective — to evaluate the effectiveness of endoscopic stent placement compared to surgical methods for the management of esophagojejunal anastomosis leakage (AL) after gastrectomy at the National Cancer Institute (NCI) from November 2017 to November 2019. Materials and methods. The study included patients receiving treatment at the Upper Gastrointestinal Oncology Department of the National Cancer Institute between November 2017 and November 2019. Throughout this period, 186 total gastrectomies were performed. 13 (6.9%) patients developed an anastomotic leak in the postoperative period. All patients had Roux‑en‑Y esophagojejunostomy. 6 patients (46.1%) underwent endoscopic stent placement in the AL area, along with perianastomotic drainage positioning and enteral feeding via a naso‑intestinal tube. Of the remaining patients, 7 (53.9%) underwent surgical treatment, including esophagostomy or esophageal stump formation with a nutritional jejunostomy. This manuscript employed methods of descriptive statistics. Results. Endoscopic stent placement was successful for 5 patients. Complete defect closure following stent placement was confirmed in 5 patients (83.3%) using endoscopic and radiological methods. The mean hospital stay in the stent group was 15.4 days (range: 9—22 days). The mean time for endoscopic stent removal during rehospitalization was 49.5 (33—62 days) days after initial placement. Complications associated with AL, specifically sepsis resulting from infection in the AL area, led to the death of 1 (16.7%) patient in the stent group. Surgical treatment was successful in 5 patients (71.4%). 2 patients (28.6%) died due to infectious complications and multiple organ failure syndrome. The average hospital stay for surgical patients was 32.8 (19—40) days. Mortality rates were 16.7% and 28.6% for the stent placement and surgical groups, respectively. Conclusions. Endoscopic endoluminal stent placement in the area of AL using self‑expandable metallic stents combined with local drainage and enteral nutrition is a promising method for treating esophagojejunal anastomotic leakage after total gastrectomy. This study demonstrates that endoscopic stent placement reduces hospital stay and mortality rates compared to surgical methods. Endoscopic stent placement provides effective defect closure with fewer complications. However, surgical treatment remains indispensable in cases of severe sepsis or failure of conservative methods, despite the high mortality risk. Further studies are needed to develop standardized approaches for selecting treatment methods based on leak size and the patient’s overall condition.